Neutrophil-to-lymphocyte and neutrophil-to-platelet ratios for predicting 28-day mortality in sepsis: A retrospective cohort study - Jianchun Wei; Xinjie Huang; Zhilian Wang; Hailing Zhang (PLoS ONE, 2026)
Objective This study aimed to evaluate the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) and neutrophil-to-platelet ratio (NPR), alone and in combination with procalcitonin (PCT), for predicting 28‑day mortality in patients with sepsis. Methods In this single‑center retrospective cohort study, 395 adult sepsis patients admitted to the emergency department between 2020 and 2025 were included. NLR and NPR were calculated from the first complete blood count obtained within 24 hours of initial emergency department presentation. Univariable Cox regression was used for preliminary screening. The C-index was used to compare the discriminative ability of traditional inflammatory markers (PCT, CRP, and WBC) to select a reference biomarker. Multivariable Cox regression and restricted cubic spline (RCS) analysis were performed to evaluate the linear and non-linear associations of NLR and NPR with mortality. To assess whether adding NLR or NPR provided incremental prognostic value to PCT, multivariable Cox models with interaction terms (PCT × NLR and PCT × NPR) were constructed. LASSO regression was applied for variable selection, and VIF was used to assess multicollinearity. Results The overall 28‑day mortality was 38.2%. Neither NLR nor NPR outperformed PCT in predicting 28-day mortality, and none of the three biomarkers showed significant independent associations with mortality after adjusting for confounders (PCT: adjusted HR per IQR = 1.02, 95% CI: 0.94–1.11, p = 0.605; NLR: HR = 1.01, 95% CI: 1.00–1.02, p = 0.235; NPR: HR = 1.00, 95% CI: 1.00–1.01, p = 0.378). Restricted cubic spline (RCS) curves confirmed no non-linear associations or threshold effects for NLR and NPR. Multivariable Cox regression with interaction terms showed that adding NLR or NPR to PCT did not provide additional prognostic value beyond PCT alone (PCT × NLR: HR = 1.00, 95% CI: 0.97–1.03, p = 0.854; PCT × NPR: HR = 0.97, 95% CI: 0.92–1.01, p = 0.121). Conclusion Neither NLR nor NPR alone, nor their combination with PCT, improved 28-day mortality prediction in this elderly sepsis cohort, suggesting that a single early measurement may be insufficient for sepsis prognostication. Future studies should explore serial measurements and integrate multiple pathophysiological dimensions. The low cost and wide availability of NLR and NPR still support their potential role within a multi-parameter panel, particularly in resource-limited settings.